Spondylodiscitis and epidural abscess - two clinical cases - Grebe, Hans Peter (2023)
Spondylodiscitis and spinal epidural abscesses are rare pathologic entities, but increasing in incidence. They often present clinically in a non-specific fashion, a fact which can Jead to diagnostic delay, with serious consequences for the patient. A high levei of suspicion is therefore necessary in order correctly diagnose such entities as quickly as possible. A patient with otherwise unexplained spinal pain should be submitted to a careful clinicai, Jaboratory, radiologic and neurologic exam. Once the diagnosis is established, adequate intravenous antibiotic treatment must be given, for at Jeast four weeks, and in the presence of neurological defects, neurosurgical intervention is often indicated. We present two cases which illustrate specific aspects of diagnosis, clinical evolution and therapeutic problems, associated with this pathology.